Cytotoxicity, acute and sub-chronic toxicities of the fruit extract of Tetrapleura tetraptera (Schumm. & Thonn.) Taub. (Fabaceae) - Idrios N. Bonsou; Armelle T. Mbaveng; Gaëlle S. Nguenang; Godloves F. Chi; Victor Kuete; Thomas Efferth (BMC, 2022)
Abstract Background Tetrapleura tetraptera is a medicinal spice traditionally used to treat cancer, diabetes, and several other ailments. This study analyzed the cytotoxicity of the dichloromethane methanol extract of T. tetraptera fruits (TTF) and its constituents. The toxicity profile of the TTF extract was also evaluated in rats. Methods The Cytotoxicity of this extract was evaluated using the resazurin reduction assay (RRA). Acute and sub-chronic toxicity studies were performed according to the protocol described by the Organisation for Economic Cooperation, and Development (OECD). Hematological, serum, and urine biochemical parameters, as well as histological sections of the liver and kidney, were also evaluated based on standard methods. Results The TTF extract, compound 5, and the reference drug doxorubicin were active in all 9 tested cancer cell lines. The recorded IC50 ranged from 18.32 μM (against B16-F1 murine melanoma cells) to 36.18 μM (against SKMel-505 BRAF wildtype melanoma cells) for TTF, from 10.02 μM (towards MaMel-80a BRAF-V600E homozygous mutant melanoma cells) to 31.73 μM (against SKMel-28 BRAF-V600E homozygous mutant melanoma cells) for compound 5, and from 0.22 μM (against B16-F1 cells) to 9.39 μM (against SKMel-505 cells) for doxorubicin. The study of acute toxicity test showed that the lethal dose (LD50) of this extract was greater than 5000 mg/kg body weight. In the sub-chronic toxicity studies, variations were observed in some biochemical parameters, especially at higher doses. Conclusion TTF and its most active compound (5) are found to be potential cytotoxic agents, meanwhile, TTF was safe when given a single oral dose of 5000 mg/kg. However, caution is necessary in case of prolonged oral administration due to potential alterations of renal function at high doses (> 1000 mg/kg).